2017
DOI: 10.1080/09540121.2017.1417528
|View full text |Cite
|
Sign up to set email alerts
|

Can we afford to offer pre-exposure prophylaxis to MSM in Catalonia? Cost-effectiveness analysis and budget impact assessment

Abstract: Pre-exposure prophylaxis (PrEP) effectiveness has been well established. This study aims to assess the cost-effectiveness of providing PrEP, estimate the number of eligible MSM, and its budget impact in Catalonia. Cost-effectiveness analysis compared costs of on daily basis and "on demand" PrEP to prevent one infection with lifetime costs of one HIV infection. We estimated the total cost of providing PrEP by estimating number of eligible MSM, and included in the budget impact assessment antiretroviral and labo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 35 publications
1
6
0
Order By: Relevance
“…Third, we conducted budget impact analysis in addition to cost-effectiveness analysis. Considering the number of MSM, our budget impact analysis demonstrated a similar result to previous studies 24 . We found introduction of PrEP program in Japan was expected to cost 708.2-897.3 million USD; this means that PrEP is an affordable intervention in Japan because national medical expenses amount to over 363.6 billion USD 25 and the cost of PrEP is likely to be covered by out-of-pocket expenses if it is approved.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Third, we conducted budget impact analysis in addition to cost-effectiveness analysis. Considering the number of MSM, our budget impact analysis demonstrated a similar result to previous studies 24 . We found introduction of PrEP program in Japan was expected to cost 708.2-897.3 million USD; this means that PrEP is an affordable intervention in Japan because national medical expenses amount to over 363.6 billion USD 25 and the cost of PrEP is likely to be covered by out-of-pocket expenses if it is approved.…”
Section: Discussionsupporting
confidence: 88%
“…Because medical checkups are required when taking PrEP, we used this proportion as the proportion eligible for PrEP. We also calculated the proportion eligible for PrEP using criteria used in other countries 24,46,47 . Using data from the same survey, we assumed that 70.0% of these men were willing to use PrEP.…”
Section: Budget Impact Analysismentioning
confidence: 99%
“…Regarding the HIV lifetime cost, in the absence of robust data for Spain, an HIV cost derived from a cost-effectiveness analysis was used. This cost included all health care inputs consumed and occupational losses generated during HIV disease, from the median age at diagnosis until death [32]. To analyse its impact on the results, an alternative HIV cost was tested in the OWSA, estimating the lifetime cost based on the annual healthcare cost by HIV patients in Spain obtained from a systematic review [43], and the life expectancy [44,45].…”
Section: Discussionmentioning
confidence: 99%
“…The HIV lifetime cost, including HIV-direct and -indirect costs, in Spain (€325,408) was identified in the literature [32] and was updated from 2015 to 2020 values.…”
Section: Model Parametersmentioning
confidence: 99%
“…Also performed in the Netherlands, the most recently reviewed study shows that 92% and 73% of the simulations were cost-effective, of which 52% and 23% were cost-saving (respectively, without and with risk compensation) [ 9 ]. In Catalonia, although at the time of the study PrEP was not approved in Spain nor was the generic drug available yet, some research suggested that PrEP would be cost-saving under a certain assumption on price reduction and its annual cost would range between €25.3–46.7 million/year (on demand PrEP), and €42.9–78.7 million/year (daily basis PrEP) [ 10 ].…”
Section: Introductionmentioning
confidence: 99%